Equity premium with habits, wealth inequality and background risk - Christos Giannikos; Georgios Koimisis (Journal of Risk and Financial Management, 2021)
In an exchange economy with endowment inequality, we investigate how preferences with external habits affect the equity risk premium. We show that the dynamics of external additive habits with wealth inequality are complex when a background risk is present. It is ambiguous whether wealth inequality will increase or decrease the equity premium even when the income uncertainty is low. This result extends literature by suggesting that wealth inequality has a small role in explaining asset pricing puzzles.
Keywords: 330; asset prices; background risk; habits; wealth inequality